Oxidative Stress and Antioxidant Pathway in Allergic Rhinitis - Munsoo Han; Dabin Lee; Sang Hag Lee; Tae Hoon Kim (MDPI AG, 2021)
Oxidative stress is the cause and consequence of redox metabolism in various physiological and pathological conditions. Understanding the molecular pathways underlying oxidative stress and the role of antioxidants could serve as the key to helping treat associated diseases. Allergic rhinitis is a condition that deteriorates the daily function and quality of life of afflicted individuals and is associated with a high socioeconomic burden and prevalence. Recent studies have focused on the role of oxidative stress and antioxidants in allergic rhinitis. This review discusses animal and clinical studies on oxidative markers and the potential therapeutic dietary antioxidants for allergic rhinitis.